The role of menstruation in women's objectification: a questionnaire study - Sveinsdottir, Herdís (Journal of advanced nursing, 2017)
Aim The aim of this study was to investigate the concepts of objectification and self‐objectification among young women in the context of attitudes towards menstruation, menstrual suppression, menstrual and menarche experiences, disorder eating and exercise habits and to detect predictors of objectification and self‐objectification. Background The negative effects of objectification are well founded. Considering the central role menstruation plays in female biology, it comes as quite a surprise that so little attention is given to the subject in the research on objectification. Design Cross‐sectional explorative survey design. Methods A questionnaire that included the Self‐Objectification Questionnaire, the Objectified Body Consciousness Scale, the Belief and Attitudes Towards Menstruation Questionnaire and the Suppress Menstruation subscale of the Attitudes Towards Menstrual Suppression Questionnaire was administered at the end of 2013 to 319 Icelandic women who represented the population by age. A stepwise multiple linear regression model was employed to calculate significant predictors of objectification and self‐objectification. Results Four models of objectification are presented: the self‐objectification model, the body surveillance model, the body shame model and the control belief model. Taken together, the strongest predictors of these models were related to eating habits. However, the findings also support the proposition that menstrual‐related experiences influence women's objectification, particularly in terms of age at menarche, of belief in the prescriptive role of menstruation and of use of pain medication for menstrual pain. Conclusion Healthcare providers in general and nurses in particular could and should assist girls and women in developing a positive view of their body and its reproductive functions by discussing the body and menstruation based on women's concerns.